Evaluating dietary supply of microminerals as a premix in a complete plant ingredient‐based diet to juvenile rainbow trout (Oncorhynchus mykiss). (22nd June 2017) - Antony Jesu Prabhu, P.; Schrama, J.W.; Fontagné‐Dicharry, S.; Mariojouls, C.; Surget, A.; Bueno, M.; Geurden, I.; Kaushik, S.J.
Abstract: Two basal diets M0 and V0 were formulated with marine and plant based ingredient composition. Seven experimental diets were prepared from the two basal diets namely M0, M100, V0, V30, V60, V100 and V150 by incorporating different levels of a micromineral premix (Cu, Fe, Mn, Se and Zn). Triplicate groups of rainbow trout (initial weight: 20 g) reared at 17°C were fed one of each diet to apparent visual satiation over 12 weeks. Among the V diet fed fish, growth and feed intake exhibited maximal response at V60 level of premix inclusion; Apparent availability coefficient of Fe, Cu and Zn decreased linearly with increasing level of premix whereas apparent availability coefficient of Mn and Se was unaffected. The available dietary concentration in basal V0 diet was for Fe, 20.6; Cu, 2.8; Mn, 6.5; Zn, 17.3 and Se, 0.195 (in mg/kg DM) and in the M0 diet for Fe, 63.3; Cu, 5.2; Mn, 2.9; Zn, 35.2 and Se, 0.87 (in mg/kg DM). In reference to NRC ( Nutrient requirements of fish and shrimp . Washington, DC: National Research Council, The National Academies Press, 2011) recommendations, the V0 basal diet accounted for 34.3%, 92.9%, 53.9%, 115% and 130.2% and the contribution from M0 diet for 105.5%, 173.3%, 24.2%, 234.7% and 580% of the minimal dietary inclusion levels of Fe, Cu, Mn, Zn and Se to rainbow trout, respectively. However, data on whole body mineral contents showed that normal levels were maintained only for Cu and Mn through supply from basal V0 diet. For Zn and Se, available supply even from the highest supplemented diet (V150) was not sufficient to maintain normal body mineral levels of rainbow trout in the present study. On the whole, optimal dietary inclusion levels of microminerals are altered while using fishmeal‐free diets for rainbow trout.